How Natural Gas can Support the Uptake of Renewable Energy - United Nations (United Nations, 2020)
There is a strong medium-to-long-term future for gas so long as it wholeheartedly embraces the energy transition and partners with renewables to produce carbon-free products, notably hydrogen, whilst embracing carbon capture and storage (CCS). Gas has several key advantages. It is highly flexible and can be used for heating, cooling, cooking, waste disposal and transportation as well as feedstock for chemicals, fertilisers and pharmaceutical products. Moreover, throughout most of the UNECE area there are already extensive distribution networks that enable gas to be transferred both across borders and within member states. These network can be adapted to carry hydrogen either mixed in with natural gas or as self-contained systems. They can also be used to distribute CO2.